2012
DOI: 10.1590/s0004-282x2012000800004
|View full text |Cite
|
Sign up to set email alerts
|

Right-to-left shunt and the hypercoagulable state: does paradoxical embolism play a role in patients with antiphospholipid syndrome and stroke?

Abstract: Patients with cryptogenic arterial ischemic stroke have a high prevalence of a patent foramen ovale (PFO) 1 . However, the simple existence of a right-to-left shunt (RLS) does not appear sufficient to explain the increased risk of ischemic stroke, and other significant factors must be required 2 . A hypercoagulable state could be one of these factors, because it increases thrombogenic mechanisms, such as venous thrombosis, which is related to paradoxical embolism (PE) 3 . Antiphospholipid syndrome (APS) is one… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 14 publications
(16 reference statements)
0
2
0
Order By: Relevance
“…1921 Few studies, however, have assessed the relationship between PFO and APS. 19,22 A previous TCD study showed a high prevalence of RLS in patients with APS (58.5%); however, there was no association between large RLS (>10 high-intensity transient signs) and stroke. 22 Conversely, one small study suggested a strong association between PFO and stroke in patients with APS.…”
Section: Discussionmentioning
confidence: 95%
“…1921 Few studies, however, have assessed the relationship between PFO and APS. 19,22 A previous TCD study showed a high prevalence of RLS in patients with APS (58.5%); however, there was no association between large RLS (>10 high-intensity transient signs) and stroke. 22 Conversely, one small study suggested a strong association between PFO and stroke in patients with APS.…”
Section: Discussionmentioning
confidence: 95%
“…Our finding supported the pathological association between PFO and CS. Except for paradoxical embolisms, increased platelet activity may be the pathogenic reasons of stroke, which may increase thrombogenic mechanisms, such as venous thrombosis 39. Thus, patients with PFO having higher MPV and increased coagulative function may be more prone to stroke.…”
Section: Discussionmentioning
confidence: 99%